2020
DOI: 10.1093/emph/eoaa003
|View full text |Cite
|
Sign up to set email alerts
|

Spondylolysis and spinal adaptations for bipedalism

Abstract: Background and objectives The study reported here focused on the aetiology of spondylolysis, a vertebral pathology usually caused by a fatigue fracture. The goal was to test the Overshoot Hypothesis, which proposes that people develop spondylolysis because their vertebral shape is at the highly derived end of the range of variation within Homo sapiens. Methodology We recorded 3D data on the final lumbar vertebrae of H. sapien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Its morphologic features indicate that UB 10749 is a lower lumbar vertebra of an early Pleistocene Homo. The dorsal wedging of the vertebral body, the widening of the inferior plate compared with the superior plate, the concavity of the inferior plate, and the ventrodorsally elongated vertebral body compared with vertebral height are all familiar lower lumbar human traits 13,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its morphologic features indicate that UB 10749 is a lower lumbar vertebra of an early Pleistocene Homo. The dorsal wedging of the vertebral body, the widening of the inferior plate compared with the superior plate, the concavity of the inferior plate, and the ventrodorsally elongated vertebral body compared with vertebral height are all familiar lower lumbar human traits 13,[20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The size, the large vertebral plate, and the relatively short vertebral body of UB 10749 indicates that it belongs to hominoidea. The lordotic wedging and the concavity of the inferior plate further suggests that this is a hominin vertebra 20,21 .…”
mentioning
confidence: 97%
“…On top of illustrating the growth of interest in shape analyses in palaeopathology, our meta‐analysis also revealed key trends that summarize how shape analyses have so far been used in palaeopathology. Overall, we identified four such themes: Describe pathological conditions and support/refute diagnoses (e.g., Berezina & Buzhilova, 2021; Berner et al, 2021; Colombo et al, 2018; Darton et al, 2015; DeSilva & Papakyrikos, 2011; Gunz et al, 2004; Hershkovitz et al, 1997; Milella et al, 2015; Rmoutilová et al, 2020; Slon et al, 2013; Thompson, 2014; Trinkaus, 2018; Vairamuthu & Pfeiffer, 2018; Viciano et al, 2017; Zhao et al, 2020) Understand how specific traits and shape characteristics predispose individuals to pathological conditions (e.g., Bédécarrats et al, 2021; Calce et al, 2018; Mansukoski & Sparacello, 2018; Mays, 2006; Plomp et al, 2012; Plomp et al, 2019; Plomp et al, 2020; Plomp, Viðarsdóttir, Weston, et al, 2015; Shepstone, 2001; Shepstone et al, 1999; Ward et al, 2010; Weiss, 2005) Identify and interpret adaptations and alterations in functional anatomy in response to pathological conditions (e.g., Berner et al, 2021; Churchill & Formicola, 1997; Gilmour et al, 2019; Lazenby & Pfeiffer, 1993; Licata et al, 2019; Micarelli et al, 2018; Roberts et al, 2004; Sparacello et al, 2016; Thompson, 2014; Trinkaus, 2018; Viciano et al, 2017; Viva et al, 2021; Zhao et al, 2020) Provide insight into aspects of physical and social experience, care practices, therapeutic interventions, and social organization (e.g., Bédécarrats et al, 2021; Chevalier, 2019; Cowgill et al, 2015; Formicola & Buzhilova, 2004; Gilmour et al, …”
Section: Sculpting a Palaeopathology Of Shapementioning
confidence: 99%
“…Situating palaeopathological data into established theoretical frameworks has and will continue to enable hypothesis‐driven research that can answer questions that are important for understanding the past, a key aim of palaeopathology, and also for understanding humans as animals that have undergone millions of years of evolution. For example, the vertebral shape traits that both Ward et al (2010) and Plomp et al (2020) identified as increasing an individual's propensity to develop spondylolysis can be explained as evolutionary adaptations for bipedalism. Both groups of researchers situated their interpretations within an evolutionary and biomechanical framework to explain why and how some humans are prone to spondylolysis.…”
Section: Sculpting a Palaeopathology Of Shapementioning
confidence: 99%
See 1 more Smart Citation